Multichannel Transcranial Direct Current Stimulation Combined With Treadmill Gait Training in Patients With Parkinson's Disease: A Pilot Study - Na, Yoonju; Kim, Jinuk; Lee, Su-Hyun; Kim, Jihye; Lee, Jungsoo; Shin, Se Young; Chang, Won Hyuk; Cho, Jin Whan; Kim, Yun-Hee (Frontiers in Neurology, 2022)
Background: Gait problems are critical impairments in Parkinson’s disease (PD), related to increased risk of falling and negatively impacting the quality of life. Transcranial direct current stimulation (tDCS) is a non-invasive brain stimulation technique that can modify the cortical excitability of gait-related brain regions. In this study, we investigated whether multichannel tDCS with simultaneous treadmill gait training could improve gait in PD. Methods: Twenty-four PD patients were assigned randomly to a real or sham tDCS group. Each patient underwent 30 minutes of treadmill gait training for 10 sessions during four consecutive weeks. 4x1 multichannel tDCS was applied using five 6 cm diameter round shape electrodes. One anode was placed on CZ, and four cathodes were positioned symmetrically over the FZ, C5, C6, and PZ. Anodal tDCS (2mA) and sham tDCS were delivered for 20 minutes. The primary outcome measure was the 10 Meter Walk Test (10MWT), and the secondary outcome measures included clinical assessment scales using the Unified Parkinson’s Disease Rating Scale (UPDRS), Timed Up and Go Test (TUG), Freezing of Gait Questionnaire (FOG-Q), Dynamic Gait Index (DGI), Berg Balance Scale (BBS), and Functional Reach Test (FRT). Participants were assessed before the intervention, immediately after the intervention, and four weeks after completion of the intervention. Results: The real tDCS group showed significant improvement in the 10MWT, but the sham group did not. Among the secondary outcome measures, UPDRS Part II, TUG, and BBS were improved only in the real tDCS group. Particularly, the UPDRS part II showed a significant group*time interaction effect which meant that real tDCS demonstrated a better effect on activities of daily living of PD patients. Conclusions: The results of this pilot study suggest that multichannel tDCS applied on the leg motor cortex during treadmill gait training is a safe and effective means to improve gait velocity in PD patients. Additional rigorous, large-sample, multicenter, randomized controlled trials are needed to confirm the effect of tDCS as a therapeutic adjunct for gait rehabilitation of PD patients.